Mathematical Models for Optimization of Tariffs in Risky Types of Insurance; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Kalashnikova T. V. Tatiana Vladimirovna (2016, 2016)
Title screen